Nutritional status of adolescent school girls residing in rural areas of Dharwad district, India: a cross sectional study - Pavithran, Sreeshma; Bant, D. D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adolescence is a period with rapid growth drive and demands higher nutrition. Improving Nutritional status of rural adolescent girls becomes the cornerstone of community’s nutritional status and target intervention for breaking intergeneration cycle of nutritional deficiencies. The objective of the study was to determine nutritional status and study the demographic factors affecting nutritional status of rural adolescent girls in Dharwad district. Methods: A cross-sectional study was carried out among 350 adolescent school girls studying in eight high schools in rural area of Dharwad district during July – September 2017. Demographic profile and dietary pattern was obtained. Anthropometric measurement and clinical examination was done. Statistical analysis was done using SSPS package. Results: Study found 14.9% of rural adolescent girls were under- weight for their age. Based on BMI, 25.2% of girls were under-nourished and 3.7% were over nourished. Significant relation with age, type of diet and age of menarche was found at p value <0.05. Conclusions: There is high prevalence of under nutrition among adolescent girls and is under nutrition is associated with micronutrient deficiencies like anaemia. There is need to create awareness to improve the nutritional needs of adolescent girls in rural areas.